Knowledge and Awareness about Radiation Protection and Hazards among Healthcare Workers in Tobruk Medical Centre - Nagat Bolowia (AlQalam Journal of Medical and Applied Sciences, 2025)
Ionizing radiation has become increasingly applied in medical practice. Accordingly, healthcare workers must be aware of radiation protection procedures and risks and apply the essential countermeasures to minimize occupational exposure. This study evaluated the awareness of radiation hazards and knowledge of radiation protection procedures among radiologists, radiographers, and nurses in diagnostic radiology departments in Tobruk Medical Center. A cross-sectional questionnaire-based study was conducted among 70 medical personnel, including radiologists, nurses, and radiographers, during the period between March and May 2022.The questionnaire collected data on demographic characteristics, awareness of radiation hazards, and knowledge of radiation protection procedures. 57.1% of contributors were males, with 42.9% between the age group of 31–40 years. 74.2% had bachelor`s degrees while 17.1% had diplomas and the minority 8.6% had higher educational degrees. Overall, all contributors showed a good level of radiation protection procedures awareness. The majority of participants (63 % + 31 %) believed that medical radiation causes a serious risk to human health. and a tiny portion of them thought it wasn’t dangerous. The current findings recommend that there is a reasonable level of awareness about radiation protection procedures and radiation hazards but a relative lack of knowledge about the As Low As Reasonably Achievable ALARA principle and 10-day rule among personnel was noticed. Therefore, continuing medical education on radiation protection and hazards must be authorized. أصبح استخدام الإشعاع المؤين مطبقًا بشكل متزايد في الممارسة الطبية. وعليه، يجب أن يكون العاملون في مجال الرعاية الصحية على دراية بإجراءات ومخاطر الحماية من الإشعاع وتطبيق التدابير المضادة الأساسية لتقليل التعرض المهني. قامت هذه الدراسة بتقييم الوعي بمخاطر الإشعاع ومعرفة إجراءات الحماية من الإشعاع بين أخصائيي الأشعة والمصورين بالأشعة والممرضات في أقسام الأشعة التشخيصية في مركز طبرق الطبي. أجريت دراسة مقطعية تعتمد على الاستبيان بين 70 من العاملين في المجال الطبي، بما في ذلك أخصائيو الأشعة والممرضات والمصورين بالأشعة، خلال الفترة بين مارس ومايو 2022. جمع الاستبيان بيانات حول الخصائص الديموغرافية والوعي بمخاطر الإشعاع ومعرفة إجراءات الحماية من الإشعاع. كان 57.1٪ من المساهمين من الذكور، و42.9٪ في الفئة العمرية 31-40 عامًا. كان 74.2٪ حاصلين على درجات البكالوريوس بينما كان 17.1٪ حاصلين على دبلومات والأقلية 8.6٪ حاصلون على درجات تعليمية أعلى. بشكل عام، أظهر جميع المساهمين مستوى جيدًا من الوعي بإجراءات الحماية من الإشعاع. اعتقدت أغلبية المشاركين (63٪ + 31٪) أن الإشعاع الطبي يسبب خطرًا خطيرًا على صحة الإنسان. واعتقد جزء صغير منهم أنه ليس خطيرًا. توصي النتائج الحالية بوجود مستوى معقول من الوعي بإجراءات الحماية من الإشعاع ومخاطر الإشعاع ولكن لوحظ نقص نسبي في المعرفة حول مبدأ أقل ما يمكن تحقيقه بشكل معقول وقاعدة العشرة أيام بين الموظفين. لذلك، يجب السماح بالتعليم الطبي المستمر حول الحماية من الإشعاع والمخاطر